Classify: Classroom Reservation Mobile Application for Students Based on Agile Development - Joy Febrianto Hale; Muhammad Taufiq Alhidayah Syah; Surya Radi Ramdhani. S (Journal of Digital Technology and Computer Science, 2025)
Classroom management in higher education often suffers from inefficiencies and scheduling conflicts as the reservation process is still carried out manually. To address these issues, this research developed Classify, an Android-based mobile application designed to help students reserve classrooms in a structured, efficient and digital way. The development followed the agile method using the Scrum framework, which was divided into three iterative sprints, including system planning, interface design with Figma, backend integration through Firebase and implementation of the main functions such as login, class list per floor, booking system and user profile management. System modeling is done with the Unified Modeling Language (UML), including Use Case Diagram and Activity Diagram. The tests are carried out using black-box and white-box methods to ensure the reliability of the system and the correctness of the program logic. The test results show that all functions work as expected and meet user requirements. Classify is thus able to improve the efficiency of the classroom reservation process, reduce the administrative burden and contribute to the digitalization of academic services in higher education.